Large Sample Neutron Activation Analysis of a Peruvian Pottery Artifact - Vasilopoulou, T.; Stamatelatos, I. E.; Montoya, E.; Bedregal, P.; Tsalafoutas, I.; Bode, P. (HNPS Advances in Nuclear Physics, 2019)
The present work was carried out within the first Large Sample Neutron Activation Analysis (LSNAA) intercomparison study organized under the auspices of the International Atomic Energy Agency (IAEA). Replicates of a Peruvian pottery object, representing a Pre-Columbian archaeological artifact, were prepared by the Instituto Peruano de Energia Nuclear (IPEN) and distributed to 10 laboratories with LSNAA capa- bilities. The LSNAA results were compared against values derived by conventional Instrumental Neutron Activation Analysis (INAA) on small amounts of the material used to produce the test object. The results of the intercomparison study will be presented in detail in a separate publication. In this work, the LSNAA methodology developed at ’Demokritos’ for analysis of large and irregular shaped objects is discussed. An accurate description of the complex geometry of the object was obtained by Computerized Tomography X-ray scanning. The correction factors required for the effects of neutron self-shielding and gamma-ray self-attenuation within the large sample material were derived by Monte Carlo simulations using MCNP code. The results of the study showed that LSNAA provides elemental concentration values with a satisfactory agreement against values obtained by conventional INAA. Therefore, LSNAA is a technique suitable for the purpose of analysis of intact pottery objects of irregular shape for archaeological studies.